2022
DOI: 10.3390/cancers14030735
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Directed Enzyme/Prodrug Therapy of Rat Brain Tumor Mediated by Human Mesenchymal Stem Cell Suicide Gene Extracellular Vesicles In Vitro and In Vivo

Abstract: MSC-driven, gene-directed enzyme prodrug therapy (GDEPT) mediated by extracellular vesicles (EV) represents a new paradigm—cell-free GDEPT tumor therapy. In this study, we tested the efficacy of yeast cytosine deaminase::uracilphosphoribosyl transferase (yCD::UPRT-MSC)-exosomes, in the form of conditioned medium (CM) to inhibit the growth of C6 glioblastoma cells both in vitro and in vivo. MSCs isolated from human adipose tissue, umbilical cord, or dental pulp engineered to express the yCD::UPRT gene secreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Recently, engineered tumor exosomes were found to act as a dendritic cell (DC)-primed vaccine, which boosted antitumor immunity in breast cancer [ 29 ]. Furthermore, MSC exosomes modified with the yCD::UPRT gene used for the experimental treatment of glioblastoma-carrying rats prevented the recurrence of glioblastoma in cured rats [ 27 ]. The prevention of UM metastases formation via the inhibition of premetastatic niche creation by yCD::UPRT -UM-sEVs seems to be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, engineered tumor exosomes were found to act as a dendritic cell (DC)-primed vaccine, which boosted antitumor immunity in breast cancer [ 29 ]. Furthermore, MSC exosomes modified with the yCD::UPRT gene used for the experimental treatment of glioblastoma-carrying rats prevented the recurrence of glioblastoma in cured rats [ 27 ]. The prevention of UM metastases formation via the inhibition of premetastatic niche creation by yCD::UPRT -UM-sEVs seems to be possible.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that extracellular vesicles (EVs) and exosomes secreted from stem cells are expected to be used as biological delivery vehicles for therapeutic agents. 48 , 49 EVs and exosomes can cross the blood-brain barrier and do not cause acute immune response and risk of tumor formation; thus, suicide gene therapy using EVs and exosomes could be a future therapeutic strategy for intracranial tumors. 50 …”
Section: Discussionmentioning
confidence: 99%
“…25,26 MSCs can be easily genetically engineered and used as biofactory for the local production of chemo and biological anticancer therapeutics at the tumor sites to overcome the challenges related to the systemic administration of anticancer therapeutics with a short half-life or high toxicity. [26][27][28] MSCs have been used for the delivery of chemotherapeutics and biological anticancer therapeutics such as genes encoding prodrug-activating enzymes, 29,30 cytokines, 31,32 oncolytic viruses, 9,33 among others. Therefore, MSCs emerged as a versatile tumor delivery vehicle in precision cancer treatment technologies for different cancers.…”
Section: Prominent Intrinsic Properties Of Msc As a Versatile Tumor D...mentioning
confidence: 99%